Development of MATLAB-Based Digital Signal Processing Teaching Module with Graphical User Interface Environment for Nigerian University - Ade', Oyetunji Samson; Ale, Daniel (International Journal of Engineering and Technology, 2013)
The development of a teaching aid module for digital Signal processing (DSP) in Nigeria Universities was undertaken to address the problem associated with non-availability instructional module. This paper annexes the potential of Peripheral Interface Controllers (PICs) with MATLAB resources to develop a PIC-based system with graphic user interface environment suitable for data acquisition and signal processing. The module accepts data from three different sources: real time acquisition, pre-recorded data acquisition and software-generated data. The developed system is able to perform analysis on both stationary and non-stationary signals using Fast Fourier Transform (FFT) and Short Time Fourier Transform (STFT). The STFT-based approach provides Improved Joint Time Frequency Analysis (IJTFA) of signals. A graphical user interface (GUI) was developed to create interactive environment for understanding the operations of digital signal processing. The developed system not only provides interactive platform for data acquisition, spectral analysis and filter design but also makes it avoidable to students in Nigeria University.